FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT RUMAH SAKIT DI PROVINSI BANGKA BELITUNG TAHUN 2017 - Fakhrulia, Dwi; Ariyanti, Fajar (Jurnal Ilmiah Keperawatan, 2021)
Performance is practical behavior as a work achievement that is produced by individuals according to their role in company. The performance of nurse is the ability of a nurse to perform nursing in accordance with their roles, functions, and responsibilities in accordance with organizational objectives. Performance can be influenced by individual characteristics and work motivation. The purpose of this study was to identify the factors that related to performance of nurse at hospital in Bangka Belitung Province in 2017. Design of this study was quantitative using a cross sectional approach. This study used secondary data from the research of health workers (Risnakes) in 2017. The data from Risnakes was analyzed from August to November 2020. The sample in this study amounted 197 nurses who worked at Hospital in Bangka Belitung Province. The statistical test used chi-square with CI 95%. The results showed that there was association between work motivation (p=0.020) with performance of nurse at hospital in Bangka Belitung Province. Meanwhile there was no association between individual characteristics (age, sex, education, marital status, working period) with performance of nurse at hospital in Bangka Belitung Province. The conclusion of this study was work motivation could affect performance of nurse at hospital in Bangka Belitung Province. Therefore the hospital leader should pay attention to improve work motivation which affect performance of nurse at hospital in Bangka Belitung Province.